2013
DOI: 10.3390/md11061920
|View full text |Cite
|
Sign up to set email alerts
|

Perna canaliculus Lipid Complex PCSO-524™ Demonstrated Pain Relief for Osteoarthritis Patients Benchmarked against Fish Oil, a Randomized Trial, without Placebo Control

Abstract: Osteoarthritis (OA) typically generates pain, reduced mobility and reduced quality of life. Most conventional treatments for osteoarthritis, such as non-steroidal anti-inflammatory drugs (NSAIDs) and simple analgesics, have side effects. PCSO-524™, a non polar lipid extract from the New Zealand Green Lipped Mussel, is rich in omega-3 fatty acids and has been shown to reduce inflammation in both animal studies and patient trials. This OA trial examined pain relief changes in relation to quality of life and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Vitamin D may reduce inflammatory pain through regulation of cytokines and macrophage activity, although more studies are warranted ( 52 ). Intervention studies with omega-3 rich oils in adults with OA have demonstrated significantly reduced pain ( 53 , 54 ), ostensibly based on anti-inflammatory mechanisms. Although not investigated in the present study, it is possible that individuals with higher pain may have taken more medications to manage the pain and been less likely to take supplements for fear of interactions or general dislike of taking multiple pills ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D may reduce inflammatory pain through regulation of cytokines and macrophage activity, although more studies are warranted ( 52 ). Intervention studies with omega-3 rich oils in adults with OA have demonstrated significantly reduced pain ( 53 , 54 ), ostensibly based on anti-inflammatory mechanisms. Although not investigated in the present study, it is possible that individuals with higher pain may have taken more medications to manage the pain and been less likely to take supplements for fear of interactions or general dislike of taking multiple pills ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%
“…P. canaliculus has been utilized in the design of commercial therapeutic agents of arthralgia in humans and animals alike. Current studies investigating the therapeutic efficacy of P. canaliculus have only produced low-level evidence, however, an indication remains that green-lipped mussels (GLMs) have therapeutic potential as adjunctive agents for rheumatoid arthritis (RA) [ 22 ], osteoarthritis (OA) [ 24 , 25 ] asthma [ 26 ] and intestinal complaints [ 27 ].…”
Section: Bioactive Molecules and Compounds From Green-lipped Mussementioning
confidence: 99%